From Manual to Digital: Transforming Hospital Nutrition with Nutri-has-Pro Application - MUSNADY; Taslim, Nurpudji Astuti; SYAUKI, Andi Yasmin; AMINUDDIN; BUKHARI, Agussalim; ASHARI, Nur (Nutrición Clínica y Dietética Hospitalaria, 2025)
Abstract: Background: Hospital malnutrition is a serious issue, often caused by inadequate food intake and underlying diseases. In Makassar, malnutrition in hospitals is 28.1%, higher than provincial and national levels. This can lead to more extended hospital stays, higher costs, and increased risks of complications. To improve care, the Nutrihas-Pro app was developed to help plan patient meals more efficiently. Automatically calculating an individual's energy requirements saves time and reduces errors, leading to better patient outcomes.; Methods: The study uses an experimental design with repeated measures to compare two methods (manual vs. app). The research was conducted over four weeks at Dr. Wahidin Sudirohusodo Hospital, Makassar. A sample of 30 participants (Residents from the Clinical Nutrition Specialist Program) were selected based on purposive sampling. In stage 1, each sample was given 2 cases of malnutrition patients to perform according to the manual calculation procedure; 2 weeks later, the same participants performed the same cases by application.; Results: The study revealed a significant difference in time efficiency between the Nutrihas-Pro app and the manual method (89.53 ± 17.52 seconds vs. 297.5 ± 39.08 seconds, p=0.000). However, both methods showed similar accuracy in calculating energy requirements, with no statistically significant difference in results (p=0.096), demonstrating that the Nutrihas-Pro app is both faster and equally accurate. Conclusions: The Nutrihas-Pro App reduced the time required for meal planning by more than 60-70%, making it a valuable tool for clinical nutritionists, especially in time-constrained environments.